2023
DOI: 10.1002/ece3.9883
|View full text |Cite
|
Sign up to set email alerts
|

Linking plant diversity–productivity relationships to plant functional traits of dominant species and changes in soil properties in 15‐year‐old experimental grasslands

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…These interactions are often due to species traits. Dietrich et al (2023) found that higher nutrient availability, possibly facilitated by legumes, benefits tall and densely rooted plant species in diverse communities, leading to greater biomass production, litter input, and soil organic carbon and nitrogen, and lower soil pH, creating a beneficial feedback loop. This knowledge can be applied to select plant species with complementary traits for grassland leys, particularly since additional benefits for the follow‐on crops could be provided (Fox et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These interactions are often due to species traits. Dietrich et al (2023) found that higher nutrient availability, possibly facilitated by legumes, benefits tall and densely rooted plant species in diverse communities, leading to greater biomass production, litter input, and soil organic carbon and nitrogen, and lower soil pH, creating a beneficial feedback loop. This knowledge can be applied to select plant species with complementary traits for grassland leys, particularly since additional benefits for the follow‐on crops could be provided (Fox et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…increased foliar elemental concentration and pools in tree foliage and accordingly higher foliage quality with higher tree diversity). Similar patterns were observed in a grassland study, where N and P decreased with plant diversity, while C concentration remained constant (Guiz et al ., 2016, 2018; Dietrich et al ., 2023). Explanations for these observations could also correspond to our findings, for example trees in mixtures might invest more nutrients into plant organs relevant for height growth instead into foliage biomass to remain competitive for other resources (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Species diversity reflects the complex relationship between organisms and their environment as well as the richness of biological resources. The aboveground biomass mirrors the vegetation characteristics and productivity of grasslands and maintains ecosystem diversity ( Hector et al., 1999 ; Dietrich et al., 2023 ). Grassland degradation contributes to the reverse transformation of the structure and function of grassland ecosystems, simultaneously weakening grassland productivity, which leads to biodiversity loss and community destabilization ( Dong et al., 2018 ; Berdugo et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%